2006
DOI: 10.1002/chem.200600203
|View full text |Cite
|
Sign up to set email alerts
|

G2(+) Investigation on the α‐Effect in the SN2 Reactions at Saturated Carbon

Abstract: As a continuing theoretical study on the alpha-effect in the S(N)2 reactions at saturated carbon centers, 28 gas-phase reactions have been examined computationally by using the high-level G2(+) method. The reactions include: Nu(-)+CH(3)X-->CH(3)Nu+X(-) (X=F and Cl; Nu(-)=HO(-), HS(-), CH(3)O(-), Cl(-), Br(-), HOO(-), HSO(-), FO(-), ClO(-), BrO(-), NH(2)O(-), and HC(==O)OO(-)). It was found that all alpha-nucleophiles examined exhibit downward deviations from the correlation line between the overall barriers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 36 publications
5
35
2
Order By: Relevance
“…Compared with the correlation, Δ H def vs. Δ H ≠ ovr , previously found in the S N 2@C reactions, the current results reveal a different situation. In fact, no Δ G ≠ ovr vs. Δ G def correlation is found for the S N 2@N reactions.…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…Compared with the correlation, Δ H def vs. Δ H ≠ ovr , previously found in the S N 2@C reactions, the current results reveal a different situation. In fact, no Δ G ≠ ovr vs. Δ G def correlation is found for the S N 2@N reactions.…”
Section: Resultscontrasting
confidence: 88%
“…Previous studies suggested that the α‐effect was not manifested in the gas phase, but it arose from solvent effect . Our research interest in the S N 2 and E2 reactions has led us to conduct several theoretical investigations on the α‐effect in recent years . Our results indicate that the α‐effect does exist in gas‐phase reactions and suggest that α‐effect is measured by the downward deviation from the plot of overall enthalpy of activation, Δ H ≠ ovr , with respect to separated reactants vs. proton affinity (PA) of n ‐Nu (or base).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Ren and Yamataka studied the reaction between several other anionic nucleophiles (HO − , HS − , CH 3 O − , HOO − , HSO − , FO − , ClO − , BrO − , NH 2 O − , HC(=O)OO − ) with CH 3 FCl and CH 3 F at the G2(+) level in the gas‐phase. Their computations indicate that nucleophiles with an adjacent lone pair ( α ‐nucleophiles) display enhanced nucleophilicity, a phenomenon known as the α ‐effect .…”
Section: Variation Of Nucleophile and Leaving Groupmentioning
confidence: 99%
“…The high and unexpected reactivity of these species is called the a-effect, and the origin of this effect has attracted the attention of many researchers. [3][4][5][6][7][8][9][10][11] In fact, it remains controversial whether the a-effect is intrinsic to the nucleophile or has its origin in the solvent effect for anionic nucleophiles. Although recent high-level theoretical calculations have provided evidence that the a-effect is intrinsic to these nucleophiles, [6][7][8] the solvent effect is very important for these reactions and also contributes for the a-effect.…”
Section: Introductionmentioning
confidence: 99%